Spatiotemporal heterogeneity of primary and secondary school student distribution in Liaoning Province, China from 2010 to 2020 - Liu, Wanbo; Zhu, Zhenghui; Wang, Ling-en (Frontiers in Earth Science, 2022)
Data mining student information helps to understand the compulsory education population size, structure, distribution and flow characteristics. Here, the spatial evolution, regional disparity, and emerging spatiotemporal distribution patterns are analyzed based on statistical data of primary and secondary education in Liaoning Province from 2010 to 2020. Demographic and spatial analysis methods, population size and structural changes were used in the assessments. The scale of primary and secondary school students in Liaoning Province declined, the gender imbalance was alleviated, and the proportion of migrant students increased. The distribution of students in primary and secondary schools is clearly unbalanced, and an increasingly evident central direction of flow from the countryside to the city exists. The overall difference in distribution of primary and secondary school students in Liaoning Province exhibits a trend of narrowing and then expanding, which is largely due to the uneven distribution among the non-agricultural municipal district, agriculture-related municipal district, and agriculture-related county. The emerging hot spot analysis patterns were dominated by consecutive and intensifying cold spots, spatiotemporal persistent and intensifying hot spots. Overall, these educational statistics and spatial analysis results provide important insights into population and educational geography.